Copolymer, composition, varnish, and cured product thereof

Aromatic vinyl compound copolymers with controlled molecular weight and vinyl group content address the softness and solubility issues of conventional hydrocarbon resins, providing a harder, solvent-soluble, and low-dielectric material for high-frequency insulation applications.

JP7627379B2Active Publication Date: 2025-02-05DENKA CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024094624
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-19
Filing Date
2024-06-11
Publication Date
2025-02-05
Estimated Expiration
2043-01-17

AI Technical Summary

Technical Problem

Conventional hydrocarbon resin-based materials for high-frequency insulation materials face challenges with softness, solvent solubility, and high dielectric properties, making them unsuitable for multilayer substrates and requiring additional fillers that further increase dielectric loss.

Method used

Aromatic vinyl compound copolymers with specific molecular weight and vinyl group content, combined with optional additives, to create a harder, solvent-soluble, and low-dielectric material suitable for insulation applications.

Benefits of technology

The solution results in a harder, solvent-soluble, and low-dielectric material suitable for high-frequency insulation, improving handling and reducing dielectric losses, suitable for multilayer substrates and electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627379000001
    Figure 0007627379000001
  • Figure 0007627379000002
    Figure 0007627379000002
  • Figure 0007627379000003
    Figure 0007627379000003
Patent Text Reader

Abstract

To solve the problem that it is difficult to prepare a varnish containing an auxiliary material in a conventional technique.SOLUTION: An aromatic vinyl compound-aromatic polyene copolymer satisfies all of the following conditions (1) to (4). (1) A number average molecular weight of a copolymer is 500 or more and less than 100,000. (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 or more and 20 or less carbon atoms, and a content of the aromatic vinyl compound monomer unit exceeds 70 mass%. (3) The aromatic polyene is one or more selected from polyenes which have a plurality of vinyl groups and / or vinylene groups in the molecule and has 5 or more and 20 or less carbon atoms, and the content of the vinyl groups and / or vinylene groups derived from the aromatic polyene unit is 2 or more and less than 30 pieces per number average molecular weight, preferably, 3 or more and less than 30 pieces. (4) One or a plurality of olefin monomer units selected from olefin monomer units having 2 or more and 20 or less carbon atoms may be contained, and the total of the olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100 mass%, when it exists together with the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copolymer, a composition, a varnish, and an insulating material obtained by curing the copolymer, a composition, a varnish, or a cured product thereof. [Background technology]

[0002] As communication frequencies move to the gigahertz band and higher, there is an increasing need for multilayer substrates made of CCL or FCCL containing insulating materials with low dielectric properties. Fluorine-based resins such as perfluoroethylene have the characteristics of excellent low dielectric constant, low dielectric loss, and excellent heat resistance, but they have difficulties in moldability and film formability, and also have issues with adhesion to copper foil in wiring, making them difficult to apply to multilayer substrates. On the other hand, substrates and insulating materials using post-curing resins such as epoxy resin, unsaturated polyester resin, polyimide resin, and phenol resin have been widely used due to their heat resistance and ease of handling, but their dielectric constant and dielectric loss are relatively high, and improvements are needed as insulating materials for high frequencies (Patent Document 1).

[0003] Therefore, attention has been focused on hydrocarbon-based resins that have inherently low dielectric properties. In order to make a hydrocarbon-based resin, which is originally a thermoplastic resin, into a curable resin, it is necessary to introduce a functional group, but functional groups that generally react to radicals or heat have polarity, which deteriorates the low dielectric properties. When attempting to introduce a functional group composed only of a hydrocarbon, for example, an aromatic vinyl group, in many cases, an intermolecular reaction between expensive hydrocarbon-based monomers is utilized (Patent Document 2), which is often not economical. Patent Document 3 shows a cured body obtained from a specific coordination polymerization catalyst and consisting of an ethylene-olefin (aromatic vinyl compound)-aromatic polyene copolymer and a non-polar vinyl compound copolymer having a specific composition and blend. In the case of this technology, only one of the two vinyl groups of the aromatic polyene (divinylbenzene) is selectively copolymerized and the remaining vinyl group is preserved, so that a crosslinkable hydrocarbon-based copolymer macromonomer having a functional group of an aromatic vinyl group can be easily obtained. Cured products obtained from similar compositions of olefin-aromatic vinyl compound-aromatic polyene copolymers and auxiliary materials and the like are characterized by low dielectric constants and low dielectric tangents (Patent Documents 4 and 5). However, the olefin-aromatic vinyl compound-aromatic polyene copolymers specifically described are relatively soft, and in order to harden them, it is necessary to blend large amounts of other hard auxiliary materials or inorganic fillers.

[0004] The low dielectric properties of known hard crosslinkable raw materials are insufficient, and when a large amount is added, the low dielectric properties of the cured body deteriorate. When a relatively large amount of inorganic filler is added, the dielectric constant of the obtained cured body becomes high because inorganic fillers generally have a high dielectric constant. In addition, a low dielectric and curable aromatic vinyl compound-aromatic polyene copolymer obtained by cationic polymerization is known (Patent Document 6), but this copolymer according to the conventional technology has many polymer end structures due to its dendritic (tree-like) structure, and the molecular design for improving heat resistance and durability is complicated due to the end structure specific to cationic polymerization contained therein. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 6-192392 [Patent Document 2] JP 2004-087639 A [Patent Document 3] JP 2007-217706 A [Patent Document 4] International Publication No. 2021 / 112087 [Patent Document 5] International Publication No. 2021 / 112088 [Patent Document 6] International Publication No. 2018 / 181842 Summary of the Invention [Problem to be solved by the invention]

[0006] The olefin-aromatic vinyl compound-aromatic polyene copolymers described in the above published patent documents are relatively soft and exhibit good solubility in solvents such as toluene, ethylbenzene, and limonene, but have insufficient solubility in solvents such as methyl ethyl ketone (MEK) which is often used as another auxiliary raw material, and therefore have the problem that it is difficult to prepare a varnish containing these auxiliary raw materials. [Means for solving the problem]

[0007] In order to solve the problems that the conventional techniques have not been able to solve, the present invention provides an aromatic vinyl compound-aromatic polyene copolymer that can give a harder cured product and has high solubility in solvents, and further provides a harder cured product that contains the aromatic vinyl compound-aromatic polyene copolymer.

[0008] That is, the present invention can provide the following aspects.

[0009] Aspect 1. An aromatic vinyl compound-aromatic polyene copolymer which satisfies all of the following conditions (1) to (4): (1) The number average molecular weight of the copolymer is 500 or more and less than 100,000. (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of aromatic vinyl compound monomer units exceeds 70 mass%. (3) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of vinyl groups and / or vinylene groups derived from aromatic polyene units is 2 or more and less than 30 per number average molecular weight. (4) One or more olefin monomer units having 2 to 20 carbon atoms may be contained, and when an aromatic vinyl compound monomer unit and an aromatic polyene monomer unit are present, the total of the olefin monomer units is 100 mass%.

[0010] Aspect 2. The aromatic vinyl compound-aromatic polyene copolymer according to embodiment 1, wherein the content of the olefin monomer unit is from 0% by mass to less than 30% by mass, relative to 100% by mass of the total of the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit, if present, and the olefin monomer unit.

[0011] Aspect 3. 3. The vinyl aromatic compound-aromatic polyene copolymer according to embodiment 2, which does not contain an olefin monomer unit.

[0012] Aspect 4. A composition comprising the aromatic vinyl compound-aromatic polyene copolymer according to any one of aspects 1 to 3, and one or more selected from the following (a) to (d): (a) Hardener (b) One or more resins selected from the group consisting of hydrocarbon elastomers, polyphenylene ether resins, and aromatic polyene resins. (c) Monomer (d) Another olefin-aromatic vinyl compound-aromatic polyene copolymer that satisfies all of the following conditions (i) to (iv): (i) The number average molecular weight of the copolymer is 500 or more and less than 100,000. (ii) The aromatic vinyl compound monomer is an aromatic vinyl compound having from 8 to 20 carbon atoms, and the content of aromatic vinyl compound monomer units is 70 mass % or less. (iii) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of the vinyl groups and / or vinylene groups derived from the aromatic polyene units is 1.5 or more and less than 20 per number average molecular weight. (iv) The olefin is one or more olefins selected from olefins having 2 to 20 carbon atoms, the content of the olefin monomer units is 30 mass% or more, and the total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100 mass%.

[0013] Aspect 5. A varnish comprising the copolymer according to any one of aspects 1 to 3 or the composition according to aspect 4, and (h) a solvent.

[0014] Aspect 6. 6. The varnish according to embodiment 5, wherein the solvent is MEK (methyl ethyl ketone).

[0015] Aspect 7. A cured product of the aromatic vinyl compound-aromatic polyene copolymer according to any one of aspects 1 to 3.

[0016] Aspect 8. A cured product of the composition according to embodiment 4.

[0017] Aspect 9. A cured product of the varnish according to aspect 5 or 6.

[0018] Aspect 10. The cured product according to any one of aspects 7 to 9, which is an electrical insulating material.

[0019] Aspect 11. A CCL substrate, an FCCL substrate, an interlayer insulating material, a bonding sheet, or a coverlay, comprising the cured product according to any one of aspects 7 to 9. Effect of the Invention

[0020] By using the aromatic vinyl compound-aromatic polyene copolymer according to the embodiment of the present invention, or a composition containing the copolymer, or a cured body or varnish made of the copolymer, a low dielectric material can be obtained which has a hard cured body and is highly soluble in solvents. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The composition according to the present invention will be described in more detail below. In this specification, the term "sheet" also includes the concept of "film." In addition, even if the term "film" is used in this specification, the term "sheet" also includes the concept of "sheet." In this specification, the term "composition" also includes the concept of "varnish." That is, among compositions, a liquid one is particularly described as "varnish." In this specification, the term "interlayer insulating material" includes the concept of a bonding sheet or an interlayer adhesive.

[0022] In this specification, ranges of values ​​are inclusive of their lower and upper limits unless otherwise specified.

[0023] <Aromatic vinyl compound-aromatic polyene copolymer> The aromatic vinyl compound-aromatic polyene copolymer of the present invention is an aromatic vinyl compound-aromatic polyene copolymer that satisfies all of the following conditions (1) to (4). (1) The number average molecular weight of the copolymer is 500 or more and less than 100,000. (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of aromatic vinyl compound monomer units is more than 70 mass%, preferably 71 mass% or more, and more preferably 80 mass% or more. (3) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of the vinyl groups and / or vinylene groups derived from the aromatic polyene units is 2 or more and less than 30, preferably 3 or more and less than 30, per number average molecular weight. (4) One or more olefin monomer units having 2 to 20 carbon atoms may be contained, and when an aromatic vinyl compound monomer unit and an aromatic polyene monomer unit are present, the total of the olefin monomer units and the aromatic vinyl compound monomer units is 100 mass%.

[0024] The olefin monomer that may be included here is at least one selected from α-olefins having 2 to 20 carbon atoms and cyclic olefins having 5 to 20 carbon atoms, and is a compound that does not substantially contain oxygen, nitrogen, or halogen and is composed of carbon and hydrogen. Examples of α-olefins having 2 to 20 carbon atoms include ethylene, propylene, 1-butene, 1-hexene, 1-octene, 1-decane, 1-dodecane, 4-methyl-1-pentene, and 3,5,5-trimethyl-1-hexene. Examples of cyclic olefins having 5 to 20 carbon atoms include norbornene and cyclopentene. The olefin that can be preferably used is a combination of ethylene with an α-olefin other than ethylene or a cyclic olefin, or ethylene alone.

[0025] The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and examples thereof include styrene, paramethylstyrene, ethylstyrene (ethylvinylbenzene), paraisobutylstyrene, various vinylnaphthalenes, and various vinylanthracenes.

[0026] The aromatic polyene monomer is a polyene having 5 to 20 carbon atoms and having multiple vinyl groups and / or vinylene groups in its molecule, preferably a polyene having 5 to 20 carbon atoms and having multiple vinyl groups in its molecule, more preferably various ortho-, meta-, and para-divinylbenzenes or mixtures thereof, divinylnaphthalene, divinylanthracene, p-2-propenylstyrene, p-3-butenylstyrene, and other aromatic vinyl structures, substantially free of oxygen, nitrogen, and halogen, and composed of carbon and hydrogen. In addition, bifunctional aromatic vinyl compounds described in JP-A-2004-087639, such as 1,2-bis(vinylphenyl)ethane (abbreviation: BVPE), can also be used. Among these, various ortho-, meta-, and para-divinylbenzenes or mixtures thereof are preferably used, and most preferably a mixture of meta-divinylbenzene and para-divinylbenzene is used. In this specification, these divinylbenzenes are referred to as divinylbenzenes. When a divinylbenzene is used as the aromatic polyene, it is preferable since the curing efficiency is high and curing is easy when a curing treatment is carried out.

[0027] The above-mentioned olefin, aromatic vinyl compound, and aromatic polyene monomers may contain other polar groups, such as olefins containing oxygen atoms, nitrogen atoms, etc., aromatic vinyl compounds containing oxygen atoms or nitrogen atoms, or aromatic polyenes containing oxygen atoms or nitrogen atoms, etc., but the total mass of these monomers containing polar groups is preferably 10 mass% or less of the total mass of the present resin composition, more preferably 3 mass% or less, and most preferably does not contain any monomers containing polar groups. By making it 10 mass% or less, the dielectric properties (low dielectric constant / low dielectric loss) of the cured body obtained by curing the present resin composition can be improved.

[0028] The present aromatic vinyl compound-aromatic polyene copolymer may preferably further satisfy the following condition (5). (5) The content of olefin monomer units is 1% by mass or more, and the total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100% by mass.

[0029] The number average molecular weight (Mn) of the copolymer is from 500 to less than 100,000. In the present invention, the number average molecular weight of from 500 to less than 100,000 means that the molecular weight calculated as standard polystyrene by GPC (gel permeation chromatography) falls within that range.

[0030] The number average molecular weight of the copolymer may be preferably 1,000 or more and 80,000 or less, more preferably 1,000 or more and 50,000 or less, and even more preferably 1,000 or more and 40,000 or less.

[0031] When the total of the aromatic vinyl compound monomer unit, the aromatic polyene monomer unit, and the olefin monomer unit present as required is taken as 100% by mass, the content of the aromatic vinyl compound monomer unit contained in the copolymer is more than 70% by mass, preferably 71% by mass or more, and more preferably 80% by mass or more. By having the content of the aromatic vinyl compound monomer unit exceed 70% by mass, the tensile modulus at 25°C of the finally obtained cured product of the aromatic vinyl compound-aromatic polyene copolymer alone can be made 1000 MPa or more, and it becomes easy to make the tensile modulus at 25°C of the cured product of the composition mainly composed of the aromatic vinyl compound-aromatic polyene copolymer 100 MPa or more. Furthermore, the aromatic vinyl compound-aromatic polyene copolymer has high solubility in solvents such as methyl ethyl ketone (MEK), making it easy to produce a varnish using methyl ethyl ketone as a solvent, for example.

[0032] The content of the aromatic vinyl compound monomer units in the copolymer may be 98% by mass or less, 95% by mass or less, 92% by mass or less, or 90% by mass or less based on the above standard. When the content of the aromatic vinyl compound monomer units is 98% by mass or less, it is easy to adjust the hardness of the cured body to an appropriate level.

[0033] In the present copolymer, the content of vinyl groups and / or vinylene groups derived from aromatic polyene units, preferably the content of vinyl groups, is 2 or more and less than 30, and preferably 3 or more and less than 30, per number average molecular weight. If the content of vinyl groups and / or vinylene groups is less than 2, the crosslinking efficiency is low, making it difficult to obtain a cured product with sufficient crosslinking density. The content of vinyl groups derived from aromatic polyene units (divinylbenzene units) per number average molecular weight in the copolymer is calculated by the number average molecular weight (Mn) calculated in terms of standard polystyrene obtained by a GPC (gel permeation chromatography) method known to those skilled in the art, and 1 The vinyl group content derived from the aromatic polyene unit obtained by H-NMR measurement can be compared. For example, 1 By comparing the intensities of the peak areas obtained by H-NMR measurement, it is found that the content of vinyl groups derived from aromatic polyene units (divinylbenzene units) in the copolymer is 0.88% by mass, and the number average molecular weight (Mn) converted into standard polystyrene by GPC measurement is 38,300. In this case, the molecular weight of the vinyl groups derived from aromatic polyene units in the number average molecular weight is the product of these values, which is 336, and dividing this by the formula weight of the vinyl groups, which is 27, gives 12.5. In other words, the content of vinyl groups derived from aromatic polyene units per number average molecular weight in this copolymer is found to be 12.5. The copolymer 1 The assignment of peaks obtained by H-NMR measurement is known from the literature. 1 A method for determining the composition of a copolymer from a comparison of peak areas obtained by H-NMR measurement is also known. 1 The H-NMR measurement method was performed in a known quantitative mode. 13 It is also possible to improve the accuracy of the composition by adding the peak areas and their ratios of the C-NMR spectrum. 13 The composition can also be determined from the peak area and ratio data of the C-NMR spectrum. In this specification, the content of divinylbenzene units in the copolymer is determined based on the peak intensity ( 1The content of divinylbenzene units is calculated from the vinyl group content derived from the divinylbenzene unit (measured by H-NMR). In other words, the content of divinylbenzene units is calculated by assuming that one vinyl group is derived from one divinylbenzene unit in the copolymer.

[0034] In the present copolymer, the content of the olefin monomer unit may be 0% by mass or more or 1% by mass or more, more preferably 0% by mass or more and less than 30% by mass or 1% by mass or more and less than 30% by mass, and even more preferably 1% by mass or more and less than 20% by mass. The total of the olefin monomer unit, aromatic vinyl compound monomer unit, and aromatic polyene monomer unit is 100% by mass. When the content of the olefin monomer unit is 1% by mass or more, the toughness (elongation) and impact resistance of the finally obtained cured body are improved, and cracks during curing or cracks during a heat cycle test of the cured body are unlikely to occur. In particular, from the viewpoint of further improving the toughness (elongation) and impact resistance of the cured body, the content of the olefin monomer unit is preferably more than 5% by mass and less than 30% by mass. In another embodiment, the present copolymer does not need to contain an olefin monomer unit.

[0035] <Method of producing aromatic vinyl compound-aromatic polyene copolymer> The aromatic vinyl compound-aromatic polyene copolymer of the present invention can be produced by copolymerizing each monomer of an aromatic vinyl compound, an aromatic polyene, and an olefin used as required by coordination polymerization. For example, it is preferable to use a single-site coordination polymerization catalyst composed of a transition metal compound and a cocatalyst, as described in JP-A-2009-161743, JP-A-2010-280771, and WO 00 / 037517, since it is possible to efficiently produce an aromatic vinyl compound-aromatic polyene copolymer.

[0036] The chemical structure of the copolymer obtained using a coordination polymerization catalyst consisting of a combination of a transition metal compound and a cocatalyst is characterized by not containing a specific structure. That is, the copolymer obtained by the cationic polymerization method according to the prior art has a polymer terminal structure containing an alicyclic ring, for example, as described in WO 2018 / 181842, but the copolymer according to the embodiment of the present invention has a notable difference in that it does not have such a structure. Due to this difference, the present invention has the effect of facilitating molecular design.

[0037] The polymer terminal structure contained in the aromatic vinyl compound-aromatic polyene copolymer of the present invention is 1 H-NMR, 13 It can be qualitatively or quantitatively clarified by a known method using C-NMR. In the aromatic vinyl compound-aromatic polyene copolymer of the present invention, the polymer end structure contained in the styrene-divinylbenzene copolymer consisting of styrene as a general aromatic vinyl compound and divinylbenzene as an aromatic polyene is one of the structures represented by the following E-1 to E-6, or any combination thereof. In addition, in the aromatic vinyl compound-aromatic polyene copolymer of the present invention, the polymer end structure contained in the ethylene-styrene-divinylbenzene copolymer consisting of styrene as a general aromatic vinyl compound, divinylbenzene as an aromatic polyene, and ethylene as an olefin as another component is one of the structures represented by the following chemical formulas E-1 to E-6, or any combination thereof.

[0038] [ka]

[0039] In the above formula, P represents a polymer structural residue of an aromatic vinyl compound-aromatic polyene copolymer, and Z represents hydrogen, a vinyl group, or a vinylene group.

[0040] The polymerization initiation terminals, which account for about half of the polymer terminal structures, are generally the above-mentioned E-1 and E-3, and in fact, most of them are E-1 and E-3. In addition, E-5 may also be included. These structures are terminals having a saturated structure, and therefore the aromatic vinyl compound-aromatic polyene copolymer of the present invention is essentially characterized by high durability such as heat resistance. The ratio of these structures changes depending on factors such as whether the first monomer insertion occurs into a metal-hydrogen bond, whether the first monomer insertion occurs into a metal-alkyl group structure, whether the first monomer insertion occurs from ethylene, styrene, or divinylbenzene, and whether the first monomer is 2,1 insertion or 1,2 insertion when styrene or divinylbenzene is used as the first monomer.

[0041] The structure of the chain transfer end (polymerization end end) of the polymer growth chain of the polymer end structure is generally E-2 and E-6, and the remaining E-5, E-4, E-1, and E-3 are also included. The proportion of the structure of the chain transfer end changes depending on whether the chain transfer occurs by hydrogen abstraction at the beta position, by chain transfer to other coordination monomers, by chain transfer to alkylaluminum, which is a cocatalyst component, or by chain transfer to a chain transfer agent such as hydrogen. In other words, the polymer end structure of the aromatic vinyl compound-aromatic polyene copolymer which may contain olefin according to the present invention is mostly saturated E-1, E-3, and E-5, and the proportion of unsaturated E-4 and E-6 is small. When an olefin other than ethylene, an aromatic vinyl compound other than styrene, or an aromatic polyene other than divinylbenzene is used, the structure is one in which each unit of ethylene, styrene, and divinylbenzene in the above-mentioned end structures E-1 to E-6 is replaced with another monomer.

[0042] The polymer end structure of the aromatic vinyl compound-aromatic polyene copolymer which may contain an olefin of the present invention is composed of at least one of the structures E-1 to E-6 described above, and does not substantially contain other structures. The aromatic vinyl compound-aromatic polyene copolymer which may contain an olefin of the present invention is obtained by a specific coordination polymerization, and is therefore a copolymer with a relatively low degree of polymer chain branching and high linearity, and the proportion of the polymer end structure itself is relatively low, and the proportion of the unsaturated end structure is even lower for the above-mentioned reason.

[0043] On the other hand, as an example of a polymer obtained by cationic polymerization, the copolymer according to the present invention does not include a terminal structure containing an alicyclic ring formed by chain transfer such as electrophilic substitution reaction of a carbocation at the polymer growth end to an aromatic ring of an aromatic monomer, which is described in WO 2018 / 181842, which is a conventional technology. On the other hand, the aromatic vinyl compound-aromatic polyene copolymer described in WO 2018 / 181842 contains a very large number of terminal structures per polymer molecule due to its dendritic, multi-branched structure, and the terminal structures described are mostly unsaturated structures of vinyl groups and vinylene groups with various structures due to cationic polymerization, which has a problem with heat resistance stability, and in particular, the relatively large amount of vinylene groups remain in the cured body even after the curing reaction, which has the problem of worsening the heat resistance stability after curing. If a large number of unsaturated groups such as vinylene groups are present in the cured body, they will bond or react with oxygen in the air, which will result in an increase in the dielectric constant and dielectric tangent of the cured body, which is not preferable.

[0044] In the present copolymer, examples of the aromatic vinyl compound-aromatic polyene copolymer (which may contain olefin) include a styrene-divinylbenzene copolymer, an ethylene-styrene-divinylbenzene copolymer, an ethylene-propylene-styrene-divinylbenzene copolymer, an ethylene-1-hexene-styrene-divinylbenzene copolymer, and an ethylene-1-octene-styrene-divinylbenzene copolymer.

[0045] The composition of the present invention may further contain, in addition to the present copolymer, (a) a curing agent, (b) one or more resins selected from a hydrocarbon-based elastomer, a polyphenylene ether-based resin, and an aromatic polyene-based resin, (c) a monomer, and (d) one or more other olefin-aromatic vinyl compound-aromatic polyene copolymers that satisfy all of the following conditions (i) to (iv): (i) The number average molecular weight of the copolymer is 500 or more and less than 100,000. (ii) The aromatic vinyl compound monomer is an aromatic vinyl compound having from 8 to 20 carbon atoms, and the content of aromatic vinyl compound monomer units is 70 mass % or less. (iii) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of the vinyl groups and / or vinylene groups derived from the aromatic polyene units is 1.5 or more and less than 20 per number average molecular weight. (iv) The olefin is one or more olefins selected from olefins having 2 to 20 carbon atoms, the content of the olefin monomer units is 30 mass% or more, and the total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100 mass%.

[0046] The other olefin-aromatic vinyl compound-aromatic polyene copolymer as the above-mentioned optional additional component may have the same characteristics as the present copolymer, except for the condition regarding the content of the aromatic vinyl compound monomer unit.

[0047] <Hardening agent> As a curing agent that can be used in the composition of the present invention, a known curing agent that can be used for the polymerization or curing of conventional aromatic polyenes and aromatic vinyl compounds can be used. Examples of such curing agents include radical polymerization initiators (radical generators), cationic polymerization initiators, and anionic polymerization initiators, and preferably radical polymerization initiators can be used. More preferably, organic peroxides and azo polymerization initiators can be used, and these can be freely selected depending on the application and conditions. A catalog listing organic peroxides can be found on the NOF Corporation website, for example. https: / / www.nof.co.jp / business / chemical / chemical-product01 It can be downloaded from. Organic peroxides are also described in the catalogs of Fujifilm Wako Pure Chemical Industries, Ltd. and Tokyo Chemical Industry Co., Ltd. The curing agent used in the present invention can be obtained from these companies. Also, a known photopolymerization initiator using light, ultraviolet light, or radiation can be used as the curing agent. Examples of the photopolymerization initiator include a photoradical polymerization initiator, a photocationic polymerization initiator, and a photoanionic polymerization initiator. Such photopolymerization initiators can be obtained, for example, from Tokyo Chemical Industry Co., Ltd. Furthermore, curing by radiation or an electron beam itself is also possible. It is also possible to perform crosslinking and curing by thermal polymerization of the raw materials contained without containing a curing agent.

[0048] There is no particular limit to the amount of the curing agent used, but generally, 0.01 to 10 parts by mass is preferred relative to 100 parts by mass of the resin composition. The resin composition is preferably free of the curing agent and solvent. When using a curing agent such as a peroxide or azo polymerization initiator, the curing process is carried out at an appropriate temperature and time, taking into consideration its half-life. In this case, the conditions are arbitrary according to the curing agent, but generally, a temperature range of about 50°C to 200°C is appropriate.

[0049] The composition or varnish according to the embodiment of the present invention may contain the total of component (b) "one or more resins selected from a hydrocarbon-based elastomer, a polyphenylene ether-based resin, and an aromatic polyene-based resin" and component (d) "another olefin-aromatic vinyl compound-aromatic polyene copolymer", preferably in the range of 1 to 200 parts by mass per 100 parts by mass of the copolymer. The addition of component (b) or component (d) has the effect of improving the mechanical properties required for various purposes of use of the cured product obtained from this varnish.

[0050] <Hydrocarbon elastomer> The amount of the hydrocarbon-based elastomer that may be contained in the composition according to the embodiment of the present invention is preferably 1 to 200 parts by mass, more preferably 1 to 100 parts by mass, and most preferably 1 to 50 parts by mass, per 100 parts by mass of the copolymer (i.e., excluding another olefin-aromatic vinyl compound-aromatic polyene copolymer, which is an optional additional component). The hydrocarbon-based elastomer that can be suitably used in the composition of the present invention preferably has a number average molecular weight of 100 to 100,000, more preferably 500 to 100,000, and even more preferably 1,000 to 4,500. The hydrocarbon-based elastomer that can be suitably used in the composition of the present invention is preferably a single or multiple elastomers selected from ethylene-based or propylene-based elastomers, conjugated diene-based polymers, aromatic vinyl compound-conjugated diene-based block copolymers or random copolymers, and hydrogenated products thereof. Examples of ethylene-based elastomers include ethylene-α-olefin copolymers such as ethylene-octene copolymer and ethylene-1-hexene copolymer, EPR, and EPDM, and examples of propylene-based elastomers include atactic polypropylene, low stereoregular polypropylene, propylene-α-olefin copolymers such as propylene-1-butene copolymer, etc. These hydrocarbon-based elastomers may be modified by introducing functional groups with maleic anhydride or other compounds.

[0051] Examples of the conjugated diene polymer include polybutadiene and 1,2-polybutadiene. Examples of the aromatic vinyl compound-conjugated diene block or random copolymer and their hydrogenated products (hydrogenated products) include SBS, SIS, SEBS, SEPS, SEEPS, SEEBS, etc. 1,2-polybutadiene that can be suitably used is available from Nippon Soda Co., Ltd. under the product names of liquid polybutadiene: B-1000, 2000, and 3000. Examples of the copolymers containing a 1,2-polybutadiene structure that can be suitably used include "Ricon100" from TOTAL CRAY VALLEY. These conjugated diene polymers and their hydrogenated products may be modified, for example, by introducing functional groups with maleic anhydride or other compounds. Among the conjugated diene polymers, polymers that do not contain vinylene groups in the main chain or have fewer vinylene groups are preferred. This is because the vinylene group in the main chain tends to remain in the cured product even after curing, and the vinylene group reacts with oxygen in the air to generate a polar group containing oxygen, which tends to increase the dielectric constant and dielectric loss value, whereas the vinyl group tends to maintain a low dielectric constant and dielectric loss tangent value after a high-temperature durability test of the cured product (for example, in air at 125°C). From this viewpoint, 1,4-polybutadiene copolymers are not suitable as the conjugated diene polymer, and preferably, 1,2-polybutadiene polymers or copolymers containing a 1,2-polybutadiene structure can be used. Furthermore, from this viewpoint, various hydrogenated polymers in which the vinylene group is hydrogenated and its content is greatly reduced can be used. Examples of hydrogenated polymers of conjugated diene polymers include hydrogenated SBR, SEBS, SEPS, SEEPS, and SEEBS, and preferably, hydrogenated polymers of conjugated diene polymers having methyl-substituted styrene may be used. When the resin or resins selected from these hydrocarbon elastomers are liquid (approximately 300,000 mPa s or less) at room temperature (25°C), in particular, the amount used is preferably 150 parts by mass or less, more preferably 1 to 30 parts by mass, and most preferably 1 to 20 parts by mass, per 100 parts by mass of the copolymer, from the viewpoints of the handleability and moldability of the composition of the present invention in an uncured state (handleability as a thermoplastic resin).

[0052] <Polyphenylene ether> As the polyphenylene ether (also referred to as "polyphenylene ether resin"), commercially available known polyphenylene ethers can be used. The number average molecular weight of the polyphenylene ether is arbitrary, and considering the moldability of the composition, the number average molecular weight is preferably 10,000 or less, and most preferably 5,000 or less. The number average molecular weight is preferably 500 or more.

[0053] In addition, when the composition of the present invention is added for the purpose of curing, it is preferable that the molecular end is modified with a functional group. In addition, when the composition of the present invention is added for the purpose of curing, it is preferable that one molecule has multiple functional groups. For example, it is preferable to use a modified polyphenylene ether. Examples of the functional group include radically polymerizable functional groups and functional groups such as epoxy groups, and preferably radically polymerizable functional groups. As the radically polymerizable functional group, a vinyl group is preferable. As the vinyl group, one or more of the group consisting of an allyl group, a (meth)acryloyl group, and an aromatic vinyl group are preferable, one or more of the group consisting of a (meth)acryloyl group and an aromatic vinyl group are more preferable, and an aromatic vinyl group is most preferable. That is, in the composition of the present invention, a bifunctional polyphenylene ether in which both ends of the molecular chain are modified with a radically polymerizable functional group is particularly preferable. Such preferred polyphenylene ethers include Noryl (trademark) SA9000 (modified polyphenylene ether having methacryloyl groups at both ends, number average molecular weight 2200) manufactured by SABIC and bifunctional polyphenylene ether oligomer (OPE-2St, modified polyphenylene ether having vinylbenzyl groups at both ends, number average molecular weight 1200) manufactured by Mitsubishi Gas Chemical Company, Inc. Allylated PPE manufactured by Asahi Kasei Corporation and aromatic polyether (ELPAC HC-F series) manufactured by JSR Corporation can also be used. Among these, bifunctional polyphenylene ether oligomer (OPE-2St) manufactured by Mitsubishi Gas Chemical Company, Inc. can be preferably used. The amount of polyphenylene ether used in the composition of the present invention is preferably 1 to 200 parts by mass, more preferably 1 to 100 parts by mass, based on 100 parts by mass of the copolymer.

[0054] <Aromatic polyene resin> The aromatic polyene resin includes a divinylbenzene reactive hyperbranched copolymer (PDV) manufactured by Nippon Steel Chemical & Material Co., Ltd. Such PDV is described, for example, in the document "Synthesis of polyfunctional aromatic vinyl copolymer and development of a new IPN type low dielectric loss material using the same" (Kawabe Masanao, Journal of Electronics Packaging Society, p. 125, Vol. 12 No. 2 (2009)). The amount of the aromatic polyene resin used in the composition of the present invention is preferably 1 to 200 parts by mass, more preferably 1 to 100 parts by mass, and most preferably 1 to 50 parts by mass, per 100 parts by mass of the copolymer. The use of the aromatic polyene resin in an amount within these ranges is preferable in order to prevent a decrease in adhesion to other members and a decrease in toughness.

[0055] <Monomer> The monomer that may be contained in the composition of the present invention is preferably 100 parts by mass or less per 100 parts by mass of the copolymer. The resin composition may not substantially contain any monomer. The monomer is a monomer that can be polymerized by any of radical polymerization, cationic polymerization, and anionic polymerization, and is preferably a monomer that can be radically polymerized. The molecular weight is preferably 5000 or less, preferably less than 5000, more preferably 1000 or less, more preferably less than 1000, even more preferably 500 or less, and further preferably less than 500, and includes the above-mentioned "aromatic vinyl compound" and "aromatic polyene", and may also appropriately include "aromatic vinylene compound". The aromatic vinylene compound is a compound having both a single aromatic ring having 9 to 30 carbon atoms or multiple condensed aromatic rings and a vinylene group. Examples of such aromatic vinylene compounds include indenes, beta-substituted styrenes, and acenaphthylenes. Examples of the indenes include indene, various alkyl-substituted indenes, and phenyl-substituted indenes. Examples of beta-substituted styrenes include β-alkyl-substituted styrenes such as β-methylstyrene, or phenyl-substituted styrenes. Examples of acenaphthylenes include acenaphthylene, various alkyl-substituted acenaphthylenes, and various phenyl-substituted acenaphthylenes. The aromatic vinylenes may be the above-exemplified compounds used alone or in combination of two or more. The aromatic vinylenes preferably have a boiling point of 175° C. or higher at normal pressure. Acenaphthylene is most preferred from the viewpoints of industrial availability and radical polymerizability. The monomer may preferably be selected from "aromatic vinyl compounds", "aromatic polyenes", or "aromatic vinylenes". The above-mentioned "aromatic vinyl compounds" and "aromatic polyenes" are preferred. More preferably, the monomer may be the following "polar monomer".

[0056] <Polar monomer> The polar monomer that may be contained in the composition of the present invention is preferably 100 parts by mass or less per 100 parts by mass of the copolymer. The resin composition of the present invention may be substantially free of polar monomers. A polar monomer is a monomer having one or more atoms selected from oxygen, nitrogen, phosphorus, and sulfur in the molecule, and a polar monomer that can be suitably used preferably has a molecular weight of less than 5000, more preferably less than 1000, and even more preferably less than 500. A polar monomer that can be suitably used in the resin composition of the present invention is preferably a polar monomer that can be polymerized by a radical polymerization initiator. Examples of polar monomers include various maleimides, bismaleimides, maleic anhydride, triallyl isocyanurate, glycidyl (meth)acrylate, tri(meth)acryl isocyanurate, and trimethylolpropane tri(meth)acrylate. Maleimides and bismaleimides that can be used in the present invention are described in, for example, International Publication No. 2016 / 114287 and JP-A-2008-291227, and can be purchased from, for example, Daiwa Kasei Kogyo Co., Ltd., Nippon Kayaku Co., Ltd., and Designer Molecules Inc. In addition, bismaleimide resin "SLK" manufactured by Shin-Etsu Chemical Co., Ltd. can also be used. These maleimide group-containing compounds are preferably bismaleimides from the viewpoints of solubility in organic solvents, high frequency characteristics, high adhesion to conductors, moldability of prepregs, etc. These maleimide group-containing compounds may be used as polyamino bismaleimide compounds from the viewpoints of solubility in organic solvents, high frequency characteristics, high adhesion to conductors, moldability of prepregs, etc. The polyamino bismaleimide compound can be obtained, for example, by subjecting a compound having two maleimide groups at the terminals to a Michael addition reaction with an aromatic diamine compound having two primary amino groups in the molecule. When attempting to obtain high crosslinking efficiency with a small amount of addition, it is preferable to use a polar monomer having a multifunctional group of two or more functional groups, such as bismaleimides, triallyl isocyanurate (TAIC), and trimethylolpropane tri(meth)acrylate. The amount of the polar monomer used in the resin composition of the present invention is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the copolymer.By using an amount within this range, the dielectric constant and dielectric dissipation factor of the obtained cured body are prevented from becoming too high; for example, the dielectric constant can be kept at 4.0 or less, preferably 3.0 or less, and the dielectric dissipation factor can be kept at 0.005 or less, preferably 0.002 or less.

[0057] <Another olefin-aromatic vinyl compound-aromatic polyene copolymer> The composition of the present invention may contain (d) one or more selected from the group consisting of olefin-aromatic vinyl compound-aromatic polyene copolymers other than the above-mentioned present copolymer, which satisfy all of the following conditions (i) to (iv): (i) The number average molecular weight of the copolymer is 500 or more and less than 100,000. (ii) The aromatic vinyl compound monomer is an aromatic vinyl compound having from 8 to 20 carbon atoms, and the content of aromatic vinyl compound monomer units is 70 mass % or less. (iii) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of the vinyl groups and / or vinylene groups derived from the aromatic polyene units is 1.5 or more and less than 20 per number average molecular weight. (iv) The olefin is one or more olefins selected from olefins having 2 to 20 carbon atoms, the content of the olefin monomer units is 30 mass% or more, and the total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100 mass%. Such olefin-aromatic vinyl compound-aromatic polyene copolymers that satisfy all of the other specific conditions are described, for example, in WO 2021 / 112087, WO 2021 / 112088, and WO 2022 / 014599. Since the olefin-aromatic vinyl compound-aromatic polyene copolymers that satisfy all of the other specific conditions are soft and exhibit a low dielectric constant and a low dielectric tangent, they are suitable for use in combination with the aromatic vinyl compound-aromatic polyene copolymer of the present invention to form a composition that provides a cured body with a low dielectric constant and a low dielectric tangent that covers a wide range of physical properties.

[0058] Specifically, for example, a composition containing preferably 1 to 200 parts by mass, particularly preferably 50 to 200 parts by mass of the other olefin-aromatic vinyl compound-aromatic polyene copolymer relative to 100 parts by mass of the aromatic vinyl compound-aromatic polyene copolymer of the present invention can further exhibit the effect of having little tackiness (self-adhesiveness) in an uncured state. In this specification, "uncured" includes the concept of semi-cured. In this specification, an uncured composition is in a state in which it exhibits thermoplasticity (i.e., a property that allows molding such as sheeting under molding conditions that do not cause curing) and can be cured by applying appropriate curing conditions (heating, pressure, etc.) after molding. Therefore, it is useful as an interlayer insulating sheet or a bonding sheet that needs to be stored or transported in an uncured state. The glass transition temperature of the aromatic vinyl compound-aromatic polyene copolymer of the present invention can be confirmed to be in the range of 30°C to 100°C by a known measurement method. The glass transition temperature of the other olefin-aromatic vinyl compound-aromatic polyene copolymer described above can be confirmed to be in the range of -100 to 30°C by a similar measurement method. Therefore, the composition as described above has a plurality of glass transition temperatures in an uncured state both in the range of 30° C. to 100° C. and in the range of −100 to 30° C. Known measuring methods include differential scanning calorimetry (DSC) and dynamic viscoelasticity measurement (DMA).

[0059] Furthermore, the composition of the present invention may contain one or more selected from the following (e) to (g): (e) Filler (f) Flame retardants (g) Surface modifier

[0060] <Filling agent> If necessary, a known inorganic or organic filler can be added. These fillers are added for the purpose of controlling the thermal expansion coefficient, controlling the thermal conductivity, and reducing the cost, and the amount used is arbitrary depending on the purpose. In particular, when adding an inorganic filler, it is preferable to use a known surface modifier, such as a silane coupling agent. In particular, when the object of the present invention is to obtain a resin composition excellent in low dielectric constant and low dielectric loss, the inorganic filler is preferably one or more of boron nitride (BN) or silica, and silica is more preferable. As the silica, fused silica is preferable. From the viewpoint of low dielectric properties, it is preferable to use 500 parts by mass or less, less than 500 parts by mass, and more preferably 400 parts by mass or less, less than 400 parts by mass of the filler relative to 100 parts by mass of the copolymer. Furthermore, in order to improve and enhance low dielectric properties (low dielectric constant, low dielectric loss tangent), a hollow filler or a filler with many voids may be added.

[0061] Instead of inorganic fillers, organic fillers such as high molecular weight polyethylene or ultra-high molecular weight polyethylene can be used. From the viewpoint of heat resistance, it is preferable that the organic fillers themselves are crosslinked, and they are preferably blended in the form of fine particles or powder. These organic fillers can suppress increases in the dielectric constant and dielectric loss tangent.

[0062] On the other hand, by mixing and dispersing a high dielectric constant insulating filler having a dielectric constant of preferably 4 to 10,000, more preferably 5 to 10,000 at 1 GHz in the resin composition of the present invention, it is possible to produce an insulating cured body having a high dielectric constant insulating layer having a dielectric constant of preferably 4 to 20 while suppressing an increase in the dielectric loss tangent (dielectric loss). By increasing the dielectric constant of a film made of an insulating cured body, it is possible to miniaturize circuits and increase the capacity of capacitors, which can contribute to miniaturization of high frequency electrical components. A high dielectric constant, low dielectric loss tangent insulating layer is suitable for applications such as capacitors, inductors for resonant circuits, filters, and antennas. Examples of the high dielectric constant insulating filler used in the present invention include inorganic fillers or metal particles that have been subjected to insulation treatment. Specific examples are known high dielectric constant inorganic fillers such as barium titanate and strontium titanate, and other examples are specifically described in, for example, JP-A-2004-087639.

[0063] <Flame retardants> A flame retardant can be used in the composition of the present invention. From the viewpoint of maintaining a low dielectric constant and a low dielectric loss tangent, preferred flame retardants are known organic phosphorus-based flame retardants such as phosphoric acid esters or condensates thereof, known bromine-based flame retardants, and red phosphorus. In particular, among phosphoric acid esters, compounds having multiple xylenyl groups in the molecule are preferred from the viewpoint of flame retardancy and low dielectric loss tangent.

[0064] In addition to the flame retardant, antimony compounds such as antimony trioxide, antimony tetraoxide, antimony pentoxide, and sodium antimonate, or nitrogen-containing compounds such as melamine, triallyl-1,3,5-triazine-2,3,4-(1H,3H,5H)-trione, and 2,4,6-triaryloxy-1,3,5-triazine may be added as a flame retardant assistant. The total amount of these flame retardants and flame retardant assistants is usually preferably 1 to 100 parts by mass per 100 parts by mass of the resin composition. In addition, 30 to 200 parts by mass of the polyphenylene ether (PPE) resin having a low dielectric constant and excellent flame retardancy may be used per 100 parts by mass of the flame retardant.

[0065] <Surface modifier> The composition of the present invention contains a surface modifier for the purpose of improving adhesion to copper foil for wiring. In particular, the purpose is to increase the adhesive strength (peel strength) to the smooth surface of copper foil. The amount of the surface modifier used is in the range of 0.001 to 10 parts by mass, more preferably in the range of 0.01 to 5 parts by mass, and most preferably in the range of 0.01 to 1 part by mass, relative to 100 parts by mass of the olefin-aromatic vinyl compound-aromatic polyene copolymer. If the amount of the surface modifier used is 10 parts by mass or less, the dielectric constant and dielectric loss tangent of the cured body obtained from the composition will be low. In the present invention, a known surface modifier can be used. Examples of such surface modifiers include silane-based surface modifiers (also known as silane coupling agents), titanate-based surface modifiers, and isocyanate-based surface modifiers, and preferably silane-based surface modifiers are used. These surface modifiers may be used singly or in combination. Such silane-based surface modifiers can be obtained from Shin-Etsu Chemical Co., Ltd., Dow Corning Co., Ltd., and Evonik Co., Ltd.

[0066] The composition of the present invention may further contain (h) a solvent. Among the compositions of the present invention, those that are particularly liquid due to the inclusion of a solvent are called varnishes.

[0067] <Solvent> An appropriate solvent may be added to the composition of the present invention as necessary. The amount of the solvent is not particularly limited. The solvent is used to adjust the viscosity and fluidity of the composition. In particular, when the resin composition of the present invention is in the form of a varnish, a solvent is preferably used. As the solvent, a solvent having a boiling point of a certain degree or higher is preferable because the thickness of the applied film becomes uniform when the boiling point is high under atmospheric pressure, that is, when the volatility is low. The preferred boiling point is about 75°C or higher under atmospheric pressure, more preferably 130°C or higher and 300°C or lower. Examples of the solvent include cyclohexane, cyclohexanone, methyl ethyl ketone (MEK), toluene, ethylbenzene, xylene, mesitylene, tetralin, acetone, limonene, mixed alkanes, mixed aromatic solvents, and the like. The amount of the solvent used in the composition of the present invention is arbitrary, but is preferably 5 to 500 parts by mass, more preferably 10 to 300 parts by mass, and most preferably 50 to 150 parts by mass, relative to 100 parts by mass of the copolymer.

[0068] When a raw material having low solubility in toluene or other aromatic solvents, such as a specific bismaleimide, is used as a component of the composition of the present invention, methyl ethyl ketone (MEK) can be used as a solvent. In this case, the aromatic vinyl compound-aromatic polyene copolymer of the present invention is preferred because it has high solubility in methyl ethyl ketone.

[0069] The composition and varnish of the present invention may contain additives that are usually used in resins, such as antioxidants, weathering agents, light stabilizers, lubricants, compatibilizers, antistatic agents, etc., within the scope of not impairing the effects and objects of the present invention. The composition and varnish of the present invention are obtained by mixing, dissolving or melting the various additives described above, and any known method can be used for mixing, dissolving and melting.

[0070] The composition of the present invention can be mixed by a known kneading method, for example, a twin-screw kneader, various rolls, various kneaders, etc. When the composition is a varnish, it can be mixed by adding it to the varnish and stirring it.

[0071] <Varnish> The varnish of the present invention can be made viscous liquid at room temperature or by heating to 100°C or less by adjusting the composition and molecular weight of the copolymer used, adding a certain amount or more of liquid monomer or solvent within the scope of the present invention, or adding a liquid flame retardant, and the viscosity at room temperature is, for example, hundreds of thousands of mPa·s or less, preferably 10,000 mPa·s or less or 2,000 mPa·s or less, more preferably 1,000 mPa·s or less, and most preferably 500 mPa·s or less. Specifically, it can be applied, impregnated, filled, or dropped onto other materials by an appropriate method, and the solvent can be removed to form a molded product. The desired cured product can be obtained by curing the varnish with heat or light. Such properties can be formed into an insulating film or insulating layer by various transfer molding (pressure molding), applying it on or between substrates or semiconductor device materials, or forming it into a sheet or film by extrusion lamination or spin coating, and then curing it. In addition, the polymerization liquid obtained when copolymerizing the aromatic vinyl compound-aromatic polyene copolymer of the present invention (which generally contains, in addition to the present copolymer, a solvent used in polymerization such as toluene, ethylbenzene, cyclohexane, methylcyclohexane, etc., residual monomers such as styrene, divinylbenzene, olefin monomers, etc., catalyst and cocatalyst components) can be used as a varnish as it is. Alternatively, a varnish can be obtained by distilling off a part or all of the solvent and residual monomers from the present polymerization liquid under reduced pressure and diluting with the above-mentioned solvent as necessary. In other words, the varnish of the present invention may contain residual monomers during polymerization and the solvent used in polymerization.

[0072] <Molded body> The shape of the molded article obtained from the composition of the present invention is arbitrary. These compositions can exhibit the properties of thermoplastic resins. Therefore, under conditions that do not cause crosslinking, the composition can be molded into shapes such as sheets, tubes, strips, and pellets in a substantially uncured state by known molding methods for thermoplastic resins, such as extrusion molding, injection molding, press molding, and inflation molding. In some embodiments, the molded article can have an effect of having little self-adhesiveness (tackiness). The molded article can then be crosslinked (cured). For example, when the composition is a varnish, it is generally formed into a sheet or film-like molded article by applying it to a substrate and removing the solvent by heating, reducing pressure, air drying, or the like. Uncured sheets and films can be obtained by these methods. A composite can also be obtained by impregnating a porous substrate, woven fabric, or nonwoven fabric with the varnish of the present invention and removing the solvent. It can also be formed into, for example, a hemispherical shape by dropping it onto a substrate and removing the solvent. The sheet may be uncured (semi-cured) to the extent that it can maintain its sheet shape, or may be completely cured. The degree of curing of the composition can be quantitatively measured by known dynamic mechanical analysis (DMA).

[0073] <Curing> The composition or varnish of the present invention, or the molded article obtained therefrom, can be cured by a known method, taking into consideration the curing conditions (temperature, time, pressure) of the raw materials and curing agent contained therein. When the curing agent used is a peroxide, the curing conditions can be determined by taking into consideration the half-life temperature and the like disclosed for each peroxide.

[0074] <Cured product obtained from the composition and cured product of the molded article> The cured product of the molded product obtained from the composition of the present invention is sufficiently cured, and the gel content measured according to ASTM is preferably 90% by mass or more, more preferably more than 90% by mass. In addition, in the measurement range of 10 to 50 GHz, particularly preferably at 10 GHz, the dielectric constant is preferably 3.0 to 2.0 or more, more preferably 2.8 to 2.0 or more, and most preferably 2.5 to 2.0 or more. The dielectric loss tangent is preferably 0.003 to 0.0005 or more, more preferably 0.002 to 0.0005 or more. In addition, the volume resistivity of the obtained cured product is preferably 1×10 15 The electrical insulating material preferably has a surface area of ​​Ω·cm or more and a water absorption rate of preferably 0.1 mass% or less, more preferably less than 0.1 mass%. These values ​​are particularly preferable for an electrical insulating material for high frequencies of, for example, 3 GHz or more.

[0075] The cured products obtained from the copolymer or composition of the present invention are particularly suitable as electrical insulating materials for high-frequency signals, and these cured products can be suitably used for CCL substrates, FCCL substrates, interlayer insulating materials (bonding sheets), or coverlays. The present invention also relates to CCL substrates, FCCL substrates, interlayer insulating materials (bonding sheets), or coverlays, which are made of the present copolymer or a composition containing the same. EXAMPLES

[0076] The present invention will be described below with reference to examples, but the present invention should not be construed as being limited to the following examples.

[0077] The copolymers obtained in the Synthesis Examples and Comparative Synthesis Examples were analyzed by the following methods.

[0078] The content of vinyl group units derived from ethylene, styrene, and divinylbenzene in the copolymer is determined by: 1 The measurements were performed using H-NMR from the peak area intensities assigned to each compound. The sample was dissolved in deuterated 1,1,2,2-tetrachloroethane, and the measurements were performed at 80 to 130°C.

[0079] The molecular weight was determined as a number average molecular weight (Mn) converted to standard polystyrene using GPC (gel permeation chromatography) under the following conditions.

[0080] Column: Two TSK-GEL MultiporeHXL-M φ7.8×300 mm (Tosoh Corporation) columns were connected in series. Column temperature: 40℃ Solvent: THF Flow rate: 1.0ml / min. Detector: RI detector

[0081] <Gel content> The gel fraction was determined as the boiling toluene insoluble matter according to ASTM D2765-84.

[0082] <Water absorption rate> The water absorption rate was measured after immersion in pure water at 23°C for 24 hours in accordance with ASTM D570-98.

[0083] <Dielectric constant and dielectric loss (dielectric tangent)> The dielectric constant and dielectric loss tangent were measured using the cavity resonator perturbation method (Agilent Technologies 8722ES network analyzer, Kanto Electronics Application Development Co., Ltd. cavity resonator) at 23°C and 10 GHz using a 1 mm x 1.5 mm x 80 mm sample cut from the sheet.

[0084] <Tensile modulus> In accordance with JIS K-6251:2017, the cured product of the composition according to each of the Examples and Comparative Examples was molded into a film sheet with a thickness of approximately 1 mm, which was then cut into a No. 2 dumbbell 1 / 2 test piece shape. The tensile modulus was measured at 25°C and a tensile speed of 500 mm / min using an Orientec Co., Ltd. Tensilon UCT-1T model.

[0085] <Storage modulus> Using a dynamic viscoelasticity measuring device (TA Instruments, formerly Rheometrics RSA-G2), measurements were taken while heating from room temperature under the condition of a frequency of 1 Hz, and the storage modulus at 280 °C was measured. A measurement sample (3 mm × 40 mm) was cut out from a film with a thickness of about 0.1 to 0.3 mm for measurement, and the storage modulus was determined. The main measurement parameters related to the measurement are as follows. Measurement frequency: 1 Hz Heating rate: 3 °C / min Sample measurement length: 10 mm Strain: 0.1%

[0086] <CTE (Coefficient of Thermal Expansion)> For CTE, referring to the 16th item of the printed wiring board material standard in the JPCA standard "Electronic Circuit Board Standard, 3rd Edition", using a thermomechanical analyzer (TMA: Thermomechanical Analyzer, manufactured by BRUKER AXS, currently manufactured by Netzsch Japan), with a width of 3 to 5 mm, a thickness of 0.5 to 0.6 mm, a distance between chucks of 15 to 20 mm, a tensile load of 10 g, and a heating rate of 10 °C / min, the measurement was carried out, and the average value between -30 °C and 150 °C was determined.

[0087] <Manufacture of Copolymer> Referring to the manufacturing methods described in JP-A-2009-161743 and JP-A-2010-280771, as a catalyst, Rac-dimethylmethylenebis(4,5-benzo-1-indenyl)zirconium dichloride (see the following formula (1) for the structure), as a cocatalyst, modified methylaluminoxane (manufactured by Tosoh Finechem Co., Ltd., MMAO-3A toluene solution), as a solvent, cyclohexane, as raw materials, styrene, divinylbenzene, ethylene, and optionally 1-hexene were used. For divinylbenzene, the product named "Divinylbenzene (96%)" (a mixture of meta and para isomers containing 96% by mass of divinylbenzene) manufactured by Nippon Steel Chemical & Material Co., Ltd. was used. Polymerization was carried out using a polymerization vessel with a capacity of 10 L, equipped with a stirrer and a heating and cooling jacket.

[0088] Synthesis Example P-1 A polymerization vessel was charged with 870g of toluene, 4530g of styrene, and 130g of divinylbenzene (meta-para mixture, 80% purity, manufactured by Nippon Steel Chemical & Materials Co., Ltd.), and the inside was thoroughly replaced with nitrogen while bubbling nitrogen with a dew point of -50°C or less into the liquid at a liquid temperature of 40°C. The gas was then switched to ethylene, and the process of pressurizing to about 0.5 MPa and releasing to normal pressure was repeated five times to replace the inside with ethylene gas. The internal liquid temperature was stabilized at 80°C, 50 mmol of modified methylaluminoxane (Tosoh Finechem, MMAO-3A toluene solution) was added as aluminum, ethylene gas was introduced, and the pressure was stabilized at 0.02 MPa (0.2 atm) by gauge, and polymerization was started by adding 50 μmol of Rac-dimethylmethylenebis(4,5-benzo-1-indenyl)zirconium dichloride (see formula (1) below for structure) and 30 ml of toluene solution containing 1 mmol of triisobutylaluminum from the catalyst tank. During polymerization, the internal temperature was maintained at 80°C, and ethylene was supplied to maintain the internal pressure at 0.02 MPa. After about 3 hours, when the specified ethylene consumption was reached, the ethylene gas was released, and a small amount of isopropanol was added to the polymerization liquid to stop the polymerization. After that, a sufficient amount of methanol was added to the obtained polymerization liquid to recover the copolymer. The copolymer was air-dried and further vacuum-dried at 30° C. for one day to obtain about 930 g of copolymer P-1. Table 1 shows the composition and number average molecular weight of the copolymer.

[0089] Formula (1) [ka]

[0090] Synthesis example P-2 Polymerization was carried out in the same manner as in P-1, except that the internal pressure of the polymerization vessel was maintained at 0.00 MPa (0.0 atm) and the internal temperature during polymerization was maintained at 100° C. About 600 g of copolymer P-2 was obtained. Table 1 shows the composition and number average molecular weight of the copolymer.

[0091] Synthesis example P-3 Polymerization was carried out in the same manner as described in JP-A-9-309925, JP-A-2009-161743, and JP-A-2010-280771, using Rac-dimethylmethylenebis(4,5-benzo-1-indenyl)zirconium dichloride (see formula (1) for structure) as a catalyst. Table 1 shows the composition and number average molecular weight of copolymer P-3.

[0092] Synthesis example P-4 Polymerization was carried out in the same manner as described in JP-A-9-40709, JP-A-9-309925, JP-A-2009-161743, and JP-A-2010-280771, using dimethylmethylenebiscyclopentadienylzirconium dichloride (see formula (2) below for structure) as a catalyst. Table 1 shows the composition and number average molecular weight of copolymer P-4.

[0093] Formula (2) [ka]

[0094] The solubility of the copolymers P-1 to P-4 in methyl ethyl ketone was examined as follows. At 25°C, 3g of copolymer granules was weighed out in a container equipped with a stirrer placed on an electronic balance, 3g of methyl ethyl ketone was added, and the mixture was stirred for 15 minutes. If the copolymer was not dissolved, the same operation was carried out while adding methyl ethyl ketone in 3g increments. The mass of methyl ethyl ketone was measured until the copolymer was completely dissolved, and the solubility was used. The solubility at 25°C was recorded in Table 1 as excellent if it was 40g or more, fair if it was 20g or more but less than 40g, and NG if it was less than 20g, when calculated based on 100g of methyl ethyl ketone.

[0095] The other raw materials are as follows: For the bifunctional polyphenylene ether oligomer (OPE-2St, modified polyphenylene ether having vinylbenzyl groups at both ends, number average molecular weight 1200), a toluene solution product manufactured by Mitsubishi Gas Chemical Company, Inc. was further diluted with toluene, and a large amount of methanol was added thereto to perform methanol precipitation. The resulting product was air-dried and then dried under reduced pressure to obtain a powdered polyphenylene ether oligomer.

[0096] 1,2-Polybutadiene (PBd): Liquid polybutadiene, "B-3000" manufactured by Nippon Soda Co., Ltd., number average molecular weight 3200, viscosity 210 Poise (45°C)

[0097] SEBS: Hydrogenated styrene-based thermoplastic elastomer, Asahi Kasei Corporation's "Tuftec H1041", number average molecular weight 58,000

[0098] The curing agent used was Perbutyl P (α,α'-di(t-butylperoxy)diisopropylbenzene) manufactured by NOF Corporation.

[0099] [Table 1]

[0100] [Table 2]

[0101] Example 1 Using a vessel equipped with a heating and cooling jacket and stirring blade, P-1 (ethylene-styrene-divinylbenzene copolymer) obtained in the synthesis example and a solvent (toluene) were heated to about 60 ° C. and stirred to dissolve the copolymer. Furthermore, 1 part by mass of a curing agent was added to 100 parts by mass of the resin components excluding the curing agent and the solvent, dissolved, stirred and mixed to obtain a varnish-like composition. The obtained composition was poured into a Teflon (registered trademark) mold (frame length 7 cm, width 7 cm, thickness 0.2 mm, 0.5 mm, or 1.0 mm) on a PET sheet placed on a glass plate, air-dried, and then dried at 60 ° C. for 3 hours or more in a vacuum dryer to obtain an uncured sheet. Furthermore, a Teflon sheet and a Teflon mold were placed under a load of 5 MPa in a press machine, and the mixture was heated at 120 ° C. for 30 minutes, 150 ° C. for 30 minutes, and then 200 ° C. for 120 minutes, and a cured sheet was obtained by removing the Teflon sheet and the Teflon mold.

[0102] Examples 2 to 6 Curable resin compositions were prepared according to the formulations in Table 2 (units in the table are parts by mass) in the same manner as in Example 1, and uncured sheets and cured sheets of the compositions of the examples were obtained in the same manner.

[0103] Comparative Examples 1 to 3 Curable resin compositions were prepared according to the formulations in Table 2 (units in the table are parts by mass) in the same manner as in Example 1, and uncured sheets and cured sheets of the compositions of the comparative examples were obtained in the same manner.

[0104] Table 2 shows the gel fraction, tensile modulus at 25° C., storage modulus at 280° C., dielectric constant, dielectric dissipation factor, coefficient of linear expansion (CTE), and water absorption of the cured sheets obtained in each of the Examples and Comparative Examples.

[0105] Table 2 also shows the results of visual inspection to determine whether the condition of the varnish was good or poor.

[0106] By comparing the cured products of P-1 and P-2 resins alone (Examples 1 and 2) with the cured products of P-3 and P-4 resins alone (Comparative Examples 1 and 2), it can be seen that all of the cured products of the copolymers of the present invention exhibit a high tensile modulus (25°C, i.e., room temperature) that satisfies the conditions of the present invention. Furthermore, the cured product of the composition of OPE-2St and P-1 (Example 5), which gives a hard cured product alone, the cured product of the composition of P-4 and P-1 (Example 3), which gives a soft cured product alone, and the cured product of the composition of 1,2-polybutadiene, SEBS, and P-1 (Example 4) also exhibit a high tensile modulus. The cured product of the composition of the present invention can easily exhibit a high tensile modulus of 100 MPa or more at room temperature. Furthermore, it was confirmed that the copolymer of the present invention and the cured sheet made of a composition containing the copolymer of the present invention exhibit a low dielectric constant and dielectric loss tangent.

[0107] As a further test, the tackiness of the uncured sheets obtained in each Example and Comparative Example was evaluated by touching with the hand. First, the uncured sheets of Examples 1, 2, and 5 were hard and had no tackiness (self-adhesiveness). The uncured sheets of Examples 3, 4, and 6 had some tackiness, but could be handled as independent sheets. The tackiness of the uncured sheets of Comparative Examples 1, 2, and 3 was higher than that of the uncured sheets of the other Examples (particularly Examples 3 and 6). In particular, the tackiness of the uncured sheets of Comparative Examples 2 and 3 was remarkably high, and it was difficult to peel off the sheets of each Comparative Example when they were adhered to each other. From this result, it was confirmed that the uncured sheets made of the copolymer of the present invention and the composition containing the copolymer of the present invention exhibited the effect of relatively reducing tackiness.

Claims

1. An olefin-aromatic vinyl compound-aromatic polyene copolymer that satisfies all of the following conditions (1) to (4): (1) The number average molecular weight of the copolymer is 500 or more and less than 100,000. (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of aromatic vinyl compound monomer units exceeds 70 mass%. (3) The aromatic polyene is one or more selected from polyenes having 10 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of the vinyl groups and / or vinylene groups derived from the aromatic polyene units is 2 or more and less than 30 per number average molecular weight. (4) The copolymer contains one or more olefin monomer units having 2 to 20 carbon atoms, the total of the aromatic vinyl compound monomer units, the aromatic polyene monomer units, and the olefin monomer units is 100 mass%, and the content of the olefin monomer units is 1 mass% or more relative to the total of the aromatic vinyl compound monomer units, the aromatic polyene monomer units, and the olefin monomer units (100 mass%).

2. The olefin-aromatic vinyl compound-aromatic polyene copolymer according to claim 1, wherein the content of the olefin monomer units is 1% by mass or more and less than 30% by mass, based on 100% by mass in total of the aromatic vinyl compound monomer units, the aromatic polyene monomer units, and the olefin monomer units.

3. A composition comprising the olefin-aromatic vinyl compound-aromatic polyene copolymer according to claim 1 and one or more selected from the following (a) to (d): (a) Hardener (b) One or more resins selected from the group consisting of hydrocarbon-based elastomers, polyphenylene ether-based resins, and aromatic polyene-based resins. (c) Monomer (d) Another olefin-aromatic vinyl compound-aromatic polyene copolymer which satisfies all of the following conditions (i) to (iv): (i) The number average molecular weight of the copolymer is 500 or more and less than 100,000. (ii) The aromatic vinyl compound monomer is an aromatic vinyl compound having from 8 to 20 carbon atoms, and the content of aromatic vinyl compound monomer units is 70 mass% or less. (iii) The aromatic polyene is one or more selected from polyenes having 10 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of the vinyl groups and / or vinylene groups derived from the aromatic polyene units is 1.5 or more and less than 20 per number average molecular weight. (iv) The olefin is one or more olefins selected from olefins having from 2 to 20 carbon atoms, the content of the olefin monomer units is 30 mass% or more, and the total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100 mass%.

4. A varnish comprising the copolymer described in claim 1 or 2, or the composition described in claim 3, and (h) a solvent.

5. 5. The varnish of claim 4, wherein the solvent is MEK (methyl ethyl ketone).

6. A cured product of the olefin-aromatic vinyl compound-aromatic polyene copolymer described in claim 1 or 2.

7. A hardened body of the composition described in claim 3.

8. A hardened body of the varnish described in claim 4.

9. The cured product according to claim 6, which is an electrical insulating material.

10. A CCL substrate, an FCCL substrate, an interlayer insulating material, a bonding sheet, or a coverlay comprising the cured body described in claim 6.

11. A CCL substrate, an FCCL substrate, an interlayer insulating material, a bonding sheet, or a coverlay comprising the cured body described in claim 7.

Citation Information

Patent Citations

  • Thermosetting resin composition having low dielectric constant

    JP1994192392A

  • Cross-copolymerized olefin-aromatic vinyl compound- diene copolymer

    JP2002322224A

  • Electronic part for high frequency using low dielectric loss tangent insulating material

    JP2004087639A

  • Cross-copolymerized olefin / styrene / diene copolymer, process for the production of the same and uses thereof

    JP2007217706A

  • Post-curable resin composition and electrical insulating material using the same

    JP2010280771A